2009
DOI: 10.1521/pedi.2009.23.6.555
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychology of Borderline Personality Disorder: Relationship With Clinical Dimensions and Comparison With Other Personality Disorders

Abstract: Patients with borderline personality disorder show various neuropsychological dysfunctions. However, the exact pattern of this dysfunction and its severity in comparison with other personality disorders are not known. The purpose of this study was to compare the neuropsychological performance of borderline patients (n = 50) with that of patients with other personality disorders (n = 30) and healthy controls (n = 30) using the Repeatable Brief Assessment of Neuropsychological Status (RBANS) test battery. Border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…This pattern parallels previous findings of medium to large effect sizes for cognitive deficits across a range of cluster A and B disorders, including schizotypal (61), antisocial (62), and borderline (63, 64) personality disorders. The main factor leading to greater overall cognitive deficits in relatives of schizophrenia probands than in relatives of bipolar probands was that relatives of schizophrenia probands as a group demonstrated cognitive deficits regardless of whether cluster A or B personality traits were present, while relatives of bipolar probands did not.…”
Section: Discussionsupporting
confidence: 88%
“…This pattern parallels previous findings of medium to large effect sizes for cognitive deficits across a range of cluster A and B disorders, including schizotypal (61), antisocial (62), and borderline (63, 64) personality disorders. The main factor leading to greater overall cognitive deficits in relatives of schizophrenia probands than in relatives of bipolar probands was that relatives of schizophrenia probands as a group demonstrated cognitive deficits regardless of whether cluster A or B personality traits were present, while relatives of bipolar probands did not.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, patients with BPD included in neuropsychological studies often present with comorbid psychiatric conditions, including major depressive disorder. In a cross-sectional study [43], borderline patients showed deficits in attention and immediate and delayed recall, with relatively preserved visuospatial and language functions compared with controls. Nevertheless, in this study, there were no significant differences between BPD and other personality disorders regarding neuropsychological deficits.…”
Section: Neutral Findings or Evidence Opposing Borderline Personalmentioning
confidence: 99%
“…Some groups have reported working memory deficits in BPD populations (14)(15)(16)(17), while others have not (18)(19)(20). In particular, one recent study reported that patients with BPD showed specific deficient attention and immediate and delayed memory (21) which correlated to impulsivity. Moreover, our group previously reported that the mechanism of actively improving recall of neutral memory contents through repetition of retrieval is impaired in BPD patients (22).…”
Section: Introductionmentioning
confidence: 99%